Evaluation of Quality of Life for Secondary School Students in Kirkuk City - salih, hewa (Iraqi National Journal of Nursing Specialties, 2016)
Objective(s):To evaluate the quality of life among secondary and to find out the relationship between students'quality of life and their socio-demographic characteristics of age, gender, residence, marital status, father's and mother's education, and family financial status in Kirkuk City. Methodology: A cross-sectional study is conducted on (100) studentwho are boys and girls aged(13 to 24) years old. These subjects are studying at secondary schools in Kirkuk City.The study is carried out at secondary schools in Kirkuk City from 7th July 7th 2014 to May 7th 2015. A questionnaire is constructed for the purpose of the study which is consisted of three parts: The first part includes the demographic data (7) items, the second part is concerned with the medical datawhich is consisted of (3) items and the third part is dealing with the quality of life of students which is consisted of (25) items to evaluate thequality of life among these students. Data are collected through the use of the questionnaire and the interview technique. They are analyzed through the application of descriptive statistical analysis approach which includes frequency, percentage, mean and mean of scores and inferential statistical data analysis approach which includes chi-squared test,T-test and analysis of variance (ANOVA) by using the statistical package of social science (SPSS) version (17). Results: The study findsthat most of the students are between (17-20) years old who are accounted for (65%). The results depict that (53%) of the sample is girl.With regard to their residence, (88%) of them are living in urban areas.Also the study concludes highly significant relationship between the quality of life of these students and their age. Recommendations: The study recommends that social worker should be present in schoolsin order to solve their problems. New center, for fathers and mothers, should be established to teach them about how to deal with the students' needs. Secondary school curriculum should include topics concerning the quality of life for these students.